Exercise in a metabolic chamber - Effects of exercise on 24 h fat oxidation - Kaito Iwayama; Kumpei Tokuyama (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Indirect calorimetry with a room-size respiratory chamber provides an ideal setting to monitor energy metabolism for a prolonged period. During the last 10 years, experiments with this method have raised interesting observations such as: 1) exercise intensity has no effect on 24 h fat oxidation, 2) exercise has little, if any, effect on 24 h fat oxidation, and 3) exercise before breakfast increases 24 h fat oxidation. To some of the scientific community and general public, the first two statements may be unacceptable. But it can be factually explained that the impact of exercise on energy metabolism is not confined to the period of physical activity itself, and that fat oxidation remains elevated during the post-exercise period. The third observation seems to be insignificant, but contradicts the second one. It is premature to conclude that exercise has no effect on 24 h fat oxidation.